Fiscal Decentralization and The Keynesian Multiplier: Evidence From Indonesian Regional Governments - Hendy Anangga Diffia; Harmono Harmono; Norman Duma Sitinjak; Diana Zuhroh (University of Merdeka Malang, 2025)
Regional revenue components affect Economic Growth through different spending allocation mechanisms in Indonesia's fiscal decentralization system. This research analyze the transmission mechanism of Local Government Revenue, Transfer Revenue, and Other Legitimate Revenues to Economic Growth through the mediation of Operating Expenditure and Capital Expenditure in 38 regencies and cities in East Java Province for the period 2019-2023. The study uses a quantitative methodology with multiple linear regression analysis and path analysis on panel data consisting of 190 observations, with data sources from the Directorate General of Fiscal Balance and the Central Statistics Agency. The findings show that all revenue components have a direct negative effect on economic growth, confirming the Keynesian economic theory that government revenue mobilization creates a contractionary effect without proper spending allocation. Operating Expenditure shows a greater influence in stimulating economic growth than Capital Expenditure. Path analysis shows that Local Government Revenue and Transfer Revenue contribute positively to Economic Growth through the mediation of Operating Expenditure. The results of the study provide fundamental policy implications for optimizing the composition of regional spending in order to maximize the fiscal multiplier effect and increase the effectiveness of economic stimulus in regional development strategies.